In the image of Origen eros, virtue and constraint in the early Christian academy - Satran, David (University of California Press, 2018)
"The most prominent Christian theologian and exegete of the third century, Origen was also an influential teacher. In the famed Thanksgiving Address, one of his students...often thought to be Gregory Thaumaturgus, later bishop of Cappadocia...delivered an emotionally charged account of his tutelage in Roman Palestine. Although it is one of the few "personal" accounts by a Christian author to have survived from the period, the Address is more often cited than read closely. But as David Satran demonstrates, this short work has much to teach us today. At its center stands the question of moral character, anchored by the image of Origen himself, and David Satran's careful analysis of the text sheds new light on higher education in the early Church as well as the intimate relationship between master and disciple"...Provided by publisher